Bimodality of incipient plastic strength in face-centered cubic high-entropy alloys. (1st January 2021) - Zhao, Yakai; Park, Jeong-Min; Jang, Jae-il; Ramamurty, Upadrasta
ABSTRACT: Spherical tip nanoindentation experiments on two typical face-centered cubic high-entropy alloys (HEAs), CoCrFeNi and CoCrFeMnNi in as-solutionized and aged conditions were performed using tips of two different radii. Large datasets of the strength at the first pop-in were obtained and their statistical nature were analyzed to gain insights into the micromechanisms responsible for the onset of incipient plasticity in HEAs that are notionally monophasic. In all the cases examined, the probability density distributions were bimodal in nature. The deconvoluted distributions were utilized to estimate the activation volumes of the underlying deformation mechanisms. They show that when the probed material's volume is relatively small, heterogeneous dislocation nucleation aided by monovacancies occurs at lower indentation stresses; this followed by homogeneous dislocation nucleation at high loads, resulting in strengths corresponding to the theoretical strengths. When a substantially larger volume is sampled, by using a larger radius tip, either the preexisting dislocation mediated ones at low stresses or vacancy cluster /grain boundary aided heterogeneous dislocations nucleation at higher stresses become dominant. Increasing the chemical short-range order in the alloy via high temperature aging leads to overall strengthening of the alloy by enhancing stress required for the homogeneous dislocation nucleation. Implications of such plurality of mechanisms with overlapping strength distributions at HEA's disposal in imparting high strength-ductility combinations are discussed. Graphical abstract: Image, graphical abstract